Lithuanian Forestry Sector Development Opportunities: Current Competitive Advantages and Possible Growth Trends - Gaižutis, Algis; Kurtinaitienė, Jolita (Ekonomika, 2007)
The purpose of the paper is to present a short summary of the current situation in the Lithuanian forestry sector, to identify the importance of the sector to the economy of the country, evaluate the main competitive advantages and to discuss the possible expansion trends for the nearest decade. The practical relevance of the research is related to the problem of Lithuanian timber and furniture industry development. The forestry sector occupies a significant part in the economy, therefore its role is very important to Lithuania. Timber industry and forestry are recognized by the Lithuanian government to be the priority sectors of the economy, therefore it is important to analyse the further development perspectives and the possible enhancement of their competitiveness. The Lithuanian forestry sector supplies important products and services to society and contributes towards the overall welfare and development. Forests comprise 7.5% of Lithuanian national property and occupy 1/3 of the territory; they supply the renewing and growing timber resources.The study was conducted using the following methods: systemic analysis and synthesis of scientific literature and statistical data sources and comparative analysis of forestry enterprises’ activity. In order to identify the main problems and perspectives of the sector, an interpretation of the secondary data sources was carried out using the economic statistical analysis and expert evaluation methods.The paper starts with describing the relevance of the topic, identifying the role of the forestry sector in the economy of Lithuania, and presenting the methods applied in the research. The current state of the forestry, timber and furniture industry as well as wood energy is presented.The forest area in Lithuania is growing from the middle of the 20th century. On 1 January 2006, Lithuania possessed 2014 thous. ha of forests (32.5% of the territory of the country) with 401.1 mill. m3 of wood. 7.6 mill. m3 of timber with bark is harvested in Lithuania every year; it comprises 58% of the total wood increment. Part of timber (about 0.1 mill. m3) is left as a post-harvesting waist on site. In the 3rd and 4th forest groups, utilisation of wood increment comprises 67%. Analysis of governmental forest inspection data suggests that Lithuania does not exploit significant reserves (about 2-2.5 mill. m3 of timber per year) to increase the supply of local timber for the industry and energy sectors. About 1.5 mill. m3 of timber per year is not delivered only from the forest reserved for the restoration of the ownership rights (which comprises 300,000 ha or 15.6% of forest area). Lithuanian industry suffers a loss of potential timber because no activity is performed in the areas until property is returned to the owners.The forestry sector produces 4% of the Lithuanian GDP. Timber industry contributes 10% to industrial value added in Lithuania. The sector involves 220 thous. private forest owners and 52 thous. workers of forestry and timber industry. This industry is among the fastest growing areas of the Lithuanian economy with a positive export-import balance (more than 60% of products are exported). The further development of the timber industry is also related to the growth of export.The second part of the paper describes the competitive advantages identified in the course of the analysis. The main competitive advantage of the timber and furniture industry is local raw materials. The producers of timber slabs are able to satisfy the growing demand of the national furniture industry. The project of vertical integration uniting producers of timber slabs and furniture components was executed successfully. Qualified human resources, experience in the field, knowledge obtained from cooperation with worldclass enterprises, as well as a strong financial capability and funding sources are promising for the growth of international competitiveness.The paper is finalised by presenting conclusions about priority business development areas and opportunities for the Lithuanian forestry sector in the next decade. It is indicated that import pressure from lower cost countries forces to review the business models: in order to increase competitiveness, producers are involved into the vertical integration from raw material supply to the end-user product (e.g., furniture supplied with wooden houses). It is forecasted that the competitive position of Lithuanian forestry sector will be enhanced by the further integration between timber raw materials and end-user products, i.e. between producers of soiled timber. wooden houses and components as well as between producers of timber slabs and furniture. A significant reorganisation is pending in the sawmill industry: old inefficient sawmills are expected to be replaced by modem sawmills that will be integrated into the production chain of value added wooden products. Advanced forestry forms are expected to be adopted in the supply of raw materials. The supply of timber raw materials will be enhanced in order to meet the increasing demands of the industry and energy sectors. The goal is to increase the supply of timber from 6.4 mill. m3 in 2005 to the level of 7.5 mill. m3 by 2010 and no less than 9.5 mill. m3 by the year 2030. In order to produce additional wood fuel, a more efficient collection of harvesting waist on site will need to be organised. In addition to the traditional forestry methods, it is suggested to apply a new, non-traditional growth system in the short turnover and plantation forests. It is concluded that the importance of the forestry sector will grow, and this is documented in a number of strategic documents adopted by the EU.